Electrical conductivity and Seebeck coefficient measurements of single nanowires by utilizing a microfabricated thermoelectric nanowire characterization platform - Wang, Z.; Adhikari, S. S.; Kroener, M.; Kojda, D.; Mitdank, R.; Fischer, S. F.; Toellner, W.; Nielsch, Kornelius; Woias, P. (Proceedings of the IEEE International Conference on Micro Electro Mechanical Systems (MEMS), 2013)
We demonstrate the fabrication and improvements of our next generation Thermoelectric Nanowire Characterization Platform (TNCP) that is utilized to investigate the thermoelectric properties of individual nanowires to obtain the Seebeck coefficient S, electrical conductivity σ and thermal conductivity κ from the same test specimen. Only from these data, the so-called figure of merit ZT can be obtained for a single nanowire. In order to analyze the structural composition of single nanowires the TNCP has also to fulfill the purpose of a sample holder used in Transmission Electron Microscopy. Our second generation of TNCPs has been designed for these purposes. As before, individual nanowires are assembled on the TNCP by means of dielectrophoresis. After this assembly the nanowire is merely physically contacted to the electrodes on the TNCP. Contact generation is in first place done by an electron beam-induced deposition (EBID) process of Pt and measurements of S and σ are carried out on individual nanowires and presented here. As the EBID process is very complex and difficult to handle we have developed a novel method using a shadow mask process for the local evaporation of platinum to generate ohmic contact between the nanowire and the surrounding electrodes. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-20